Herding in a Concentrated Market: a Question of Intent - Holmes, Phil (2013)
While considerable evidence exists that institutions herd, the issue of why herding takes place remains unresolved. Using monthly holdings data for Portugal, we find clear evidence of herding and investigate whether such behaviour is intentional or spurious. By analysing herding under different market conditions, we conclude it is intentional. Month-of-the-quarter analysis suggests reputational reasons drive behaviour. Results are consistent with herding interacting with window dressing to determine funds, buy and sell decisions. The findings are important in understanding market dynamics and fund managers' behaviour and are of great significance to investors in managed funds.